Development Factors of Public Facilities in Coastal Reclamation Land of Lamongan Regency Case Study of Syech Maulana Ishaq Tomb Area Kemantren Village, Lamongan - Alfan Fikri Fathoni; RA Retno Hastijanti; Darmansjah Tjahja Prakasa (International Conference of Innovation and Community Engagement, 2024)
The northern coastal area of Lamongan Regency is a priority area for the development of Regency development and is one of the minapolitan areas in Indonesia [1]. The coastal area of Lamongan Regency from year to year experiences rapid growth and development in various sectors that can cause damage to the coastal environment and marine ecosystems [2]. In addition to the fisheries sector, economic improvement in Lamongan is also driven by the tourism sector, especially religious tourism in Kemantren village where the Tomb of Sheikh Maulana Ishaq is located. one of them is the development of public facility development along the coast of Lamongan regency which chooses reclaimed land as land for the development of public facilities [3]. Therefore, it is important to conduct research to determine the development factors of public facilities that use reclaimed land as land for public facility development. The method used in this research uses a qualitative method by using data search methods obtained from interviews and direct observation in real life which will be described descriptively. Based on the results of the study, it shows that there are several factors that influence the development of public facility development on reclaimed land, one of which is from an architectural point of view, the building will be easily recognised and remembered because of its iconic design and has a panoramic beauty value that can increase the attractiveness of visitors, from an economic point of view, the increasing attractiveness of visitors to visit will be able to increase the economic income of the public facility further.